THE INFLUENCE OF MOTIVATION AND PERCEPTIONS ON CULTURAL TOURISM ON TOURIST LOYALTY IN TOURIST ATTRACTIONS IN SAMUT SONGKHRAM - Sintam, Romklao (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The objectives of this research were: (1) to investigate the level of motivation, perceptions on cultural tourism and tourist loyalty in tourist attractions in Samut Songkhram, and (2) investigate the influence of motivation and perceptions on cultural tourism on tourist loyalty in tourist attractions in Samut Songkhram. The research was quantitative. The questionnaire was used as the tool for data collection. The sample consisted of 400 tourists in Samut Songkhram Province. Data analysis employed descriptive statistics, including mean, standard deviation. Inferential statistics included Pearson correlation analysis and multiple regression analysis with Enter method. The research results were revealed as follows: (1) The mean of motivation was at a high level (= 4.12). The aspect with the highest average was Physical (= 4.29). The mean of perceptions on cultural tourism was at a high level ( = 4.15). The aspect with the highest average was tourist attraction (= 4.20). The mean of tourist loyalty was at a high level (= 4.20). The aspect with the highest average was intention to revisit (= 4.22). (2) Motivation had a significant positive correlation with tourist loyalty at a level of 0.01. The correlation coefficient of motivation was 0.271. Perceptions on cultural tourism had a significant positive correlation with tourist loyalty at a level of 0.01. The correlation coefficient of perceptions on cultural tourism was 0.502. (3) Motivation significantly affected tourist loyalty (beta=0.317) and perceptions on cultural tourism significantly affected tourist loyalty in tourist attractions in Samut Songkhram (beta=0.261) at a level of .01.